Electrochemical dehydrogenation of hydrazines to azo compounds. Issue 7 (6th March 2019) - Du, Ke-Si; Huang, Jing-Mei
Abstract : A strategy for the electrochemical dehydrogenation of hydrazine compounds is disclosed under ambient conditions. Its synthetic value is well demonstrated by the highly efficient synthesis of symmetric and unsymmetric azo compounds. It is an environmentally friendly transformation and the present protocol was effective on a large scale. Abstract : A strategy for the electrochemical dehydrogenation of hydrazine compounds is disclosed under ambient conditions. This protocol proceeded smoothly in ethanol by employing electrons as clean oxidants. Its synthetic value is well demonstrated by the highly efficient synthesis of symmetric and unsymmetric azo compounds. It is an environmentally friendly transformation and the present protocol was effective on a large scale.